Technical and economic indicators of the use of liquefied natural gas in road transport - D. A. Dryuchin; S. V. Gorbachev (Интеллект. Инновации. Инвестиции, 2022)
Road transport plays an important role in the life of modern society, satisfying the transport needs of almost all sectors of the economy and the population. Mass motorization has led to a number of problems, the severity of which is increasing every day. The most urgent problems are caused by the negative impact of motor transport on the environment and the problems associated with the release of greenhouse gasses that lead to climate change on a planetary scale. According to many experts, one of the most difficult and one of the most promising methods to reduce the severity of these problems is the use of liquefied natural gas as an automobile fuel. Scientific and applied developments in this direction are largely innovative in nature. Assessment of technical and economic indicators of their practical implementation will determine the area of effective application and identify key consumers of this fuel and energy scheme. The purpose of the study is to improve the efficiency of the operation of motor vehicles based on the results of the analysis of technical and economic indicators of using liquefied gas as an automobile fuel. The achievement of the designated goal is ensured by solving such tasks as analysis of technological and technical and economic parameters of the use of liquefied methane; development of an algorithm for conducting technical and economic analysis, formalization of input data and parameters; testing of the developed algorithm in practice, obtaining the results of technical and economic analysis; generalization of the results obtained, formulation of conclusions and practical recommendations. Due to the lack of accumulated experience in the practical operation of vehicles using liquefied methane, the methods of mathematical modeling of the object of study and multi-criteria analysis conducted with respect to the data obtained from the results of modeling are applied in the work. The main result of the study is an established multidimensional domain determined by a combination of key parameters such as fuel cost, vehicle cost, its annual mileage and other parameters. These multidimensional areas constitute the scientific novelty of the results of the performed research. The overlay of the identified multidimensional area on the area formed on the basis of the analysis of the structural parameters of the regional fleet of vehicles allows you to identify key consumers and generate the data necessary to determine the infrastructure parameters that ensure the implementation of the technology in question. One of the promising areas of further research within the framework of the designated topic is the development of a methodology for the formation of infrastructure parameters that ensure the effective use of liquefied methane as an automobile fuel.